NORMOTENSIVE PHEOCHROMOCYTOMA-CASE REPORT - Ivana Mladenovska Stojkoska; Brankica Krstevska; Biljana Todorova; Sasho Dohcev (My University, 2014)
We present a patient 32 years old with accidentally discovered tumor of the right adrenal gland with transabdominal ultrasound. Computer tomography scanning of the adrenal glands showed a tumor in the right adrenal gland with heterogeneous structure with large hypodenses zones and irregular margins,7x5 sm in diametar. The patient doesn,t have any symptoms and signs suggestive of adrenal disease(Sy.Cushing or Feochromocytoma).The patient has an abdominal pain and fatique.Blood pressure was 100/70 mm Hg, TT-66 kg, 173 cm TV (BMI 22 kg/m2). Hormonal test evaluation showed the following results: VMA = 2 Metanefrin= 44.9 in 24 h/urina, basal plasma cortisol level = 309.7 nmol / l and 80.10 nmol / l after suppression with 1 mg tabl.dexamethasone (lowe-doses dexamethasone suppression test),Na + = 140 mmol / l, K + = 4.3 mmol / l. Hormonal test evaluation showed non-hormonal active tumor. Radioraphy of lungs was with normal finding.Surgery, as the treatment of choice was recommended because of the sise of the tumor and the age of the patient. The patien was treat with laparoscopic adrenalectomy and the tumor was removed with the postoperative course without complication.Histopathological finding and immunocystochemistry is addition to malignant pheochromocytoma.After surgery were measured elevated levels of chromogranin A = 420 ng/ml.To proof metastatic disease was performed scintigraphy of somatostatin receptors and PET scan for possible further treatment with ablative dose and MJBG or chemotherapy. This is the first case of normotensive, non-hormonal active malignant pheochromocytoma published in our medical literature.
Keywords: "Silent" pheochromocytoma; hormonal tests; surgery; pathologically finding